(untitled) (Configurazioni. Research on contemporary poetry, 2023)
The dichotomy between "mapping" and "selection", at the foundation of the anthologies of the twentieth century, is radicalized in the contemporary panorama, which sees the field of poetry contested between the macro-areas of lyric and experimentation. The anthological choices of the 2000s seem more oriented towards a militancy restricted to a specific field (and generation), with a loose gaze on the surrounding environment and on phenomena (such as "prose in prose") destined for a long-lasting impact that is still entirely to check.